Becoming [compact disc] : (original motion picture score) - Washington, Kamasi, 1981-; Washington, Kamasi, 1981- (Young Turks, 2020)
Kamasi Washington composed and produced the original score for the four-time Emmy-nominated film that provided an intimate glimpse into the life of Michelle Obama. Produced by Netflix Originals, it documented a moment of profound change for the former First Lady, not only for her personally but for the country she and her husband served over eight years in the White House. Washington, who joined the project in its embryonic stages, provides the powerful musical backdrop.